Erginlerin Evlat Edinilmesi ve Koşulların Değerlendirilmesi - Çelik, Nazlı Hilal (Legal Yayıncılık, 2021)
Evlat edinme, ana ve baba ile çocuk arasında soybağının kurulmasını sağlar. Türk Hukukunda küçüklerin ve erginlerin evlat edinilmeleri farklı düzenlemelere tabiidir. Bu çalışmada erginlerin evlat edinilmeleri tarihsel süreçler de dikkate alınarak Türk ve İsviçre Hukuklarında karşılaştırmalı olarak incelenmiştir.

Adoption ensures the establishment relationship between parents and children. Adoption of minors and adults is subject to different regulations in Turkish Law. In this study, adoption of adults was examined comparatively in Turkish and Swiss Laws, taking into account historical processes.
Adults Adoption and Evaluation of Conditions
Keywords: Erginlerin Evlat Edinilmesi; Evlat Edinilme; Evlat Edinmeden Doğan Hısımlık; Evlat Edinmenin Sonuçları; Evlat Edinmenin Genel Koşulları; Erginlerin Evlat Edinilmesine Özgü Koşullar; Adults Adoption; Adoption; Kinship by Adoption; Consequences of Adoption; General Requirement of Adoption; Requirement Specific to the Adoption of Adults